Bimbingan Teknis Penerapan Jatidiri Koperasi: Program Perkuatan bagi Pengurus Koperasi Primer dan Sekunder di Jawa Barat - Yuanita Indriani (LPPM Universitas Koperasi Indonesia, 2023)
The business scale of cooperatives in the province of West Java is quite heterogeneous, both in termsof business scale and type of business, and the number of members less beneficial to its members,because the cooperative is managed not in accordance with the identity of the cooperative. This hasprompted the Office of Cooperatives and UMKM of West Java Province to provide technicalguidance to Cooperative Management so that they can manage cooperatives in accordance withCooperative identity. Community Service Activities that are packaged in Technical Guidanceactivities are carried out with the aim of improving and/or perfecting the management of cooperativebusinesses and organizations so that cooperatives can provide the highest possible benefits formembers so that this technical guidance activity is more about awareness activities for cooperativeManagement that managing cooperative organizations and businesses are different from managingnon-cooperative companies, cooperatives must be able to create the highest possible benefits formembers, cooperatives are learning and democratizing organizations, so cooperative strategicdecisions must be made through member meetings. At the end of the technical guidance session, eachmember draws up an action plan to improve and improve the management of the cooperative'sorganization and business so that it conforms to the identity of the cooperative, in the end, can beexpected that the cooperative will provide the highest benefits for its members and become a people'seconomic movement.